Study On The Effect Of Alumina Reinforcements On Fe-Cr Matrix Composite - Shamsuddin, Saidatulakmar (2011)
Metal Matrix Composites (MMCs) have shown significance improvement from intellectual interest in scientific world to the technological and commercial applications for over the past three decades. In the present study, an attempt to fabricate a new MMC of Fe-Cr matrix composites reinforced with Al2O3 particles through conventional Powder Metallurgy (PM) method was successfully obtained. No phases other than the constituent were developed in the composites after sintering.